2018
DOI: 10.1097/ccm.0000000000003132
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Administration of Ramelteon, a Melatonin Receptor Agonist, on the Duration of Stay in the ICU: A Single-Center Randomized Placebo-Controlled Trial*

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 24 publications
(20 reference statements)
1
99
1
3
Order By: Relevance
“…Similar to melatonin, few adverse events are reported with the medication, but sleep promotion was not proven and the cost is higher than that of melatonin. One recent single-center, double-blind, placebo-controlled RCT, also not included in this analysis, found that the administration of 8 mg of ramelteon at 20:00 hours each day to critically ill adults without delirium was associated with significant reduction in delirium occurrence (521).…”
Section: Melatoninmentioning
confidence: 99%
“…Similar to melatonin, few adverse events are reported with the medication, but sleep promotion was not proven and the cost is higher than that of melatonin. One recent single-center, double-blind, placebo-controlled RCT, also not included in this analysis, found that the administration of 8 mg of ramelteon at 20:00 hours each day to critically ill adults without delirium was associated with significant reduction in delirium occurrence (521).…”
Section: Melatoninmentioning
confidence: 99%
“…Another group analyzed melatonin levels in general medicine vs ICU patients and found that ICU patients have a blunted release of nightly melatonin compared to non‐ICU patients . One of the only studies to date examining the use of a melatonin agonist (ramelteon) in ICU patients was recently published . The primary outcome of the study, ICU length of stay, was not found to be significantly reduced in the ramelteon group; however, a secondary finding of occurrence of ICU delirium was significantly lower (24.4% in the ramelteon group vs 46.5% in the placebo group, p = 0.044).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the administration of nightly low‐dose exogenous melatonin to elderly patients in hospital wards resulted in a lower incidence of delirium . In addition, a recent study found that administration of ramelteon, a melatonin receptor agonist, decreased patients’ ICU length of stay . The optimal melatonin dosage and impact on the incidence of delirium in critically ill patients, however, remains unknown.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies evaluating the benefit of pharmacological agents to promote sleep with an impact on clinical outcomes have been lacking. In the past year, studies using dexmedetomidine and ramelteon have suggested a great role for pharmacological promotion of sleep as a way to reduce the risk for delirium and improvement in other related clinical outcomes such as length of stay, while studies with propofol have not suggested a similar benefit consistently . Given this growing body of literature, the ICU pharmacist will take a greater role promoting sleep in the ICU and serving as the pharmacotherapy expert within this realm.…”
Section: Discussionmentioning
confidence: 99%